Why is there no revolution in North-Korea? The political economy of revolution revisited - Thomas Apolte (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
In this paper the political economy of revolutions is revisited, as it has been developed and applied in a number of publications by Acemoglu and Robinson. We criticize the fact that these authors abstract from collective-action problems and focus on inequality of income or wealth instead. In doing so, they reanimate a long but misleading tradition in social sciences, namely to directly deduct prospective group behavior from the collective interest of a group. We show that, because of collective-action problems, income inequality is not a sufficient condition for a revolution to occur. Furthermore, we also show that inequality does not even need to be a necessary condition, since all what is needed in order for a group to be interested in a revolution is that this group as a whole can expect to be a beneficiary of a revolution. For the latter to apply, however, inequality is not necessary. Hence, not inequality but rather a certain structure of commitment devices or their absence is crucial for explaining why revolutions sometimes occur and sometimes not.
Keywords: D72; D74; O15; P16; 330; Credible Commitments; Dictatorship; Political Economy; Redistribution